2017
DOI: 10.17508/cjfst.2017.9.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Annual variations of Fusarium mycotoxins in unprocessed maize, wheat and barley from Bosnia and Herzegovina

Abstract: SummaryIn this study, the occurrence of Fusarium mycotoxins deoxynivalenol (DON), zearalenone (ZEA) and fumonisins (FUM) was investigated in a total of 257 samples of unprocessed cereals (maize, wheat and barley), sampled annually in Bosnia and Herzegovina throughout the 2013-2015 harvesting period. The levels of mycotoxins were determined using a validated ELISA method. The results showed maize to be the most contaminated cereal among the three, with DON detected in 85%, ZEA in 73% and FUM in 67% of samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…1533.80 µg/kg), and Dobrogea (max. 1326.40 µg/kg) (Table 1 [57,64,[75][76][77][79][80][81][82]90,[128][129][130][131][132][133]. The geographic distribution of Fusarium spp.…”
Section: Deoxynivalenol Occurrence In the Triticale Crop And Other Cereals By Soil Typementioning
confidence: 99%
“…1533.80 µg/kg), and Dobrogea (max. 1326.40 µg/kg) (Table 1 [57,64,[75][76][77][79][80][81][82]90,[128][129][130][131][132][133]. The geographic distribution of Fusarium spp.…”
Section: Deoxynivalenol Occurrence In the Triticale Crop And Other Cereals By Soil Typementioning
confidence: 99%
“…The areas of prevalence of each mycotoxin are currently changing, due to climate change, and a wide variability in the quality and quantity of contamination has recently been reported [35,36], suggesting that mycotoxins are the most important food safety hazard affected by climate change [37]. Aflatoxins, still mentioned as a cause of death in African countries [38][39][40][41][42] are now spreading over a wider area, especially in Europe [43][44][45][46], and an increase in the risk of contamination has also been predicted in the future [47].…”
Section: Mycotoxigenic Fungi: the Main Risk Affecting Cereal Productionmentioning
confidence: 99%
“…In 2013-2015, research into mycotoxins in cereals in the area of Bosnia and Herzegovina investigated a total of 58 barley samples for the presence of mycotoxins DON, ZEN, and fumonisins by the ELISA method. The published data showed that DON was detected totally in 22 samples (38%) in quantifiable concentrations with the average content of 365 µg/kg and the highest detected values of 578 µg/kg, ZEN was found in 20 samples (34%) with the highest measured concentration of 84 µg/kg (Pleadin et al 2017). We can state that considering different weather conditions and used analytical methods the occurrence of the studied mycotoxins is comparable.…”
Section: The Effect Of the Variety And Previous Crop On The Mycotoxin Contentmentioning
confidence: 69%
“…Modified forms of mycotoxins represent new research trends (Freire & Sant'ana 2018). Cereals may be simultaneously contaminated with two or more mycotoxins (Běláková et al 2014;Pleadin et al 2013Pleadin et al , 2017, detection of one mycotoxin may indicate the presence of another, and this contamination influences the cumulative toxic effect.…”
mentioning
confidence: 99%